Clinical Actionability of the Genomic Landscape of Metastatic Castration Resistant Prostate Cancer - Devlies, Wout (Cells, 2020)
The development of targeted therapies increases treatment options for metastatic castration resistant prostate cancer (mCRPC) patients. There is a need for strong predictive and prognostic signatures to guide physicians in treating mCRPC patients. In this review we unravel the possible actionability in the AR pathway, PI3K AKT signaling, and DNA repair pathways. Additionally, we make recommendations on biomarker trial design, and the clinical use of this new type of data.